Analysis, behavior, and market performance of sweet corn (Zea mays L. sacharata) certified structure in Leban Hamlet, Tawangargo Village, Karangploso Sub-District, Malang District - Novita Kartika Kusuma Wardani; Budi Setiawan; Abdul Wahib Muhaimin; Fitria Dina Riana; Dina Novia Priminingtyas (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: Tawangargo Village, Karangploso District, Malang Regency is the largest sweet corn producing region in Karangploso District with a business base on developing vegetables that lead to special environmentally friendly products in Leban Hamlet. Quality assurance for fresh food with excellent certification requirements. The resulting product is safe for consumption or safe for pesticides. Sweet corn marketing system helps marketing institutions related to farmers in accessing consumers, making the price of sweet corn at the farm level with the price of corn accessed by different consumers. This research tries to analyze the market structure, study the market and improve the sweet corn market in Leban Hamlet, Tawangargo Village. Method: The basic method of research is analytical descriptive. Determining the location of research carried out intentionally or intentionally. Farmer sampling method using census method, with a total sample of 9 respondents. The sampling method used by traders uses the snowball sampling method with the number of broker 1 respondent and 1 respondent village collector. Data were analyzed by SCP (Structure, conduct, and performance) methods. Results: The results showed the structure of the sweet corn market in Leban Hamlet, Tawangargo Village has a tendency in imperfectly competitive markets namely the oligopsonistic market. This structure is completed inefficient markets. Market behavior discusses the marketing activities of sweet corn in Leban Hamlet. While the market performance (market performance) is 50%. Conclusion: This shows that the marketing of sweet corn in Leban Hamlet is included in the efficient category.